Тhe Role of Japan in Providing Assistance to Armenians and in Developing Several Sectors of the Economy of Armenia - Harutyunyan, Yeva (History and Culture, 2022)
The information about the beginning of Armenian-Japanese cooperation goes back to the 19th century, which mostly referred to the commercial sphere. Japan has always been interested in the fate of Armenians. Since 1894, the Japanese press has regularly covered the mass killings of Armenians in the Ottoman Empire, as well as the Armenian Genocide in 1915. In 1922 the first international humanitarian aid fund, headed by Eiichi Shibusawa, was opened in Japan to support Armenian Genocide survivors. Japan also showed a great support to Armenians during 1988’s earthquake in Spitak city. After the collapse of the Soviet Union and the restoration of independence of the Republic of Armenia, Armenian-Japanese relations were limited only to economic assistance provided by Japan in an attempt to rehabilitate the dilapidated economic and social structures of Armenia. Since 1992, the economic policy of Japan in Armenia has been observed in three stages according to the type of assistance provided by Japan to Armenia such as grants, loans and technical equipment. Since 2018, there has been noticed a tendency towards equal partnership in the field of economy and in the development of mutually beneficial economic relations between Armenia and Japan.